Prediction Of Implantation Results In Vitro Fertilization And Intracytoplasmic Sperm Injection Using Data Mining Methods (The Peerian Journal, 2024)
In vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) are two important subtypes of assisted reproductive technologies used to treat infertility. Predicting the outcome of IVF/ICSI implantation or the likelihood of pregnancy is essential for infertile couples as these treatments are complex and expensive, and the probability of conception is low.